2017
DOI: 10.1371/journal.pone.0189670
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2/STAT3 inhibitor pacritinib effectively inhibits patient-derived GBM brain tumor initiating cells in vitro and when used in combination with temozolomide increases survival in an orthotopic xenograft model

Abstract: PurposeThe prognosis for patients diagnosed with glioblastoma multiforme (GBM) remains dismal, with current treatment prolonging survival only modestly. As such, there remains a strong need for novel therapeutic strategies. The janus kinase (JAK)2/signal transducer and activator of transcription (STAT)3 pathway regulates many cellular processes in GBM, including survival, proliferation, invasion, anti-apoptosis, and immune evasion. Here, we evaluated the preclinical efficacy of pacritinib, a novel compound tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…Thus, these findings indicate a strong correlation between WP1066 and programmed cell death. Currently, WP1066 is being investigated for brain metastasis in clinical trials (NCT01904123) [83,86]. Similarly, another study by Tsujita et al showed that WP1066 demonstrated efficacy by promoting apoptosis of bladder cancer cells [84].…”
Section: Targeting Jaksmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these findings indicate a strong correlation between WP1066 and programmed cell death. Currently, WP1066 is being investigated for brain metastasis in clinical trials (NCT01904123) [83,86]. Similarly, another study by Tsujita et al showed that WP1066 demonstrated efficacy by promoting apoptosis of bladder cancer cells [84].…”
Section: Targeting Jaksmentioning
confidence: 99%
“…Pacritinib was also well tolerated and adverse events were uncommon, with patients generally presenting mild gastrointestinal toxic effects. In another study, Jensen and colleagues used patient-derived brain tumor-initiating cells and demonstrated that pacritinib was able to reduce cell viability in these cells with satisfactory results [86]. Moreover, the team determined the compatibility of pacritinib in combination with temozolomide, the current standard of care chemotherapy for glioblastoma multiforme.…”
Section: Targeting Jaksmentioning
confidence: 99%
“…The expression of STAT-3 (Signal Transducer and Activator of Transcription 3) could be considered a marker for M2 polarized GAMs and it is activated in GBMs cells as well. The JAK2/STAT-3 pathway regulates many cellular processes in GBM, including cell survival, proliferation, invasion, anti-apoptosis, and immune evasion making STAT-3 a possible target of therapy [ 92 , 93 ].…”
Section: Gliomasmentioning
confidence: 99%
“…The activation of STAT3 is associated with a worse prognosis and more aggressive disease than those with lower levels of activated STAT3 [ 7 , 8 , 9 ]. Inhibition of STAT3 has been reported to inhibit proliferation of GBM cells and attenuate resistance to temozolomide, which has translated into survival benefits based on in vivo models [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%